The histological development of the fetal human inferior colliculus during the second trimester - Nanda, Reetuparna; Bota, Mihail; Jayakumar, Jaikishan; S, Suresh; Lata, S.; Kumar, E. Harish; Srinivasan, Chitra; Vasudevan, Sudha; Jayaraman, Kumutha; Sivaprakasam, Mohanasankar; Verma, Richa (Frontiers in Neuroanatomy, 2025)
The inferior colliculus (IC) is an important midbrain station of the auditory pathway, as well as an important hub of multisensory integration. The adult mammalian IC can be subdivided into three nuclei, with distinct cyto- and myeloarchitectonical profiles and distinct calcium binding proteins expression patterns. Despite several studies about its structural and functional development, the knowledge about the human fetal IC is rather limited. In this paper we first systematically describe the histological development of the human fetal IC and its subparts in five stages of the second trimester of pregnancy: 15 gestation weeks (GW), 18 GW, 21 GW, 24 GW, and 27 GW. We 3D reconstruct and calculate the volumetric growth of IC from one stage to another, which increases from 12.85 mm3 at 15 GW to 34.27 mm3 at 27 GW in the left hemisphere. The volumetric changes in the IC were further evaluated at the cellular level using serial Nissl-stained sections, as well as glial fibrillary acidic proteins (GFAP) and calretinin immunohistochemistry. We identify stellate-like and round neurons in the central nucleus of the IC (CNIC) at 24 GW and 27 GW, comparable to the adult human IC. Novel in this study, we investigate the differential calretinin expression patterns in the IC subparts, from 15 GW to 27 GW. CR labeling is identified mainly in the cortical IC rather than in the central nucleus. Furthermore, using GFAP, we describe the radial glial fibers patterns in IC, which are dominant at 18 GW and gradually taper off at later developmental stages. Finally, we describe the development of astroglia in each of the five developmental stages. All these results indicate that the human fetal IC development and cellular maturation occur in two major stages during the second trimester.